2015
DOI: 10.14810/ijamse.2015.4401
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Magnesium Lithium Alloy Elastic Constants

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…It has been found that the averaged values of the elastic moduli of a single crystal of the Mg-5% Li (wt.) alloy have the value 𝐸 𝑐 = 56.5 GPa; 𝐸 𝑎 = 41.5 GPa and differ from those given in [20] by no more than 4.8% and 7.5%, respectively. The ultimate tensile strength and yield strength of a single crystal of the alloy Mg-5 % Li (wt.)…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It has been found that the averaged values of the elastic moduli of a single crystal of the Mg-5% Li (wt.) alloy have the value 𝐸 𝑐 = 56.5 GPa; 𝐸 𝑎 = 41.5 GPa and differ from those given in [20] by no more than 4.8% and 7.5%, respectively. The ultimate tensile strength and yield strength of a single crystal of the alloy Mg-5 % Li (wt.)…”
Section: Discussionmentioning
confidence: 56%
“…Estimates of the elasticity modulus after the abovementioned types of processing using the found Kearns texture parameters and the elasticity constants of a single crystal of the Mg-5% Li (wt.) alloy, taken from [20], showed that the calculated and experimental values of the elasticity modulus of the alloy sheets differ by no more than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the values of crystalline domains sizes D, lattice distortion ε, dislocations density ρ, elastic modulus E, and damage parameters ω are mainly due to the crystallographic texture formed during thermomechanical processing and cycle's number of subsequent alternating bending of sheets. The corresponding regularities have been described by regression equations ( 14) -( 19), as well as (21)(22)(23)(24)(25)(26). екструзією, прокаткою після екструзії (в поєднанні з відпалом і зміною напрямку прокатки) і подальшого знакозмінного вигину (ЗІ) з числом циклів 0,5, 1, 3 і 5 на модуль пружності (E), параметр накопичення пошкоджень (параметр пошкоджуваності ω), кристалографічну текстуру і параметри субструктури бінарного сплаву Mg -5% Li (ваг.).…”
Section: Discussionunclassified
“…The elastic constants of the Mg-5%Li alloy were calculated by us earlier [23]. The results are shown in Table 1.…”
Section: Eejp 1 (2020)mentioning
confidence: 99%